COSA Minutes & Agenda, August 2019 - Council on Staff Affairs, Valdosta State University (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 2019)
Council On Staff Affairs (COSA) meeting Minutes and agenda. August 2019.
Council On Staff Affairs (COSA) Meeting Agenda, August 20, 2019. Valdosta State University. 1 electronic document, 4 pages. Council On Staff Affairs (COSA) Minutes of Tuesday August 20, 2019. Valdosta State University. 1 electronic document, 10 pages.
Keywords: Council on Staff Affairs (Valdosta State University); Committees; Electronic records; Minutes (Records)